2015
DOI: 10.1210/jc.2015-1176
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 Receptor Agonist Treatment Increases Bone Formation and Prevents Bone Loss in Weight-Reduced Obese Women

Abstract: Treatment with a long-acting GLP-1 RA increased bone formation by 16% and prevented bone loss after weight loss obtained through a low-calorie diet, supporting its role as a safe weight-lowering agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
79
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(91 citation statements)
references
References 52 publications
9
79
2
1
Order By: Relevance
“…Despite limitations in the methods used to determine the above-mentioned changes in bone mass, changes in bone turnover markers observed in this study also supported a favorable effect of liraglutide [86]. Indeed, there were significant, 11%-16% increases in plasma concentrations of the bone formation markers P1NP and osteocalcin during liraglutide treatment, in contrast to non-significant changes in the control group.…”
Section: Glp-1 Receptor Agonistssupporting
confidence: 65%
See 2 more Smart Citations
“…Despite limitations in the methods used to determine the above-mentioned changes in bone mass, changes in bone turnover markers observed in this study also supported a favorable effect of liraglutide [86]. Indeed, there were significant, 11%-16% increases in plasma concentrations of the bone formation markers P1NP and osteocalcin during liraglutide treatment, in contrast to non-significant changes in the control group.…”
Section: Glp-1 Receptor Agonistssupporting
confidence: 65%
“…There was a significant decrease in plasma vitamin D concentrations in the control group, in contrast to a non-significant decrease in the liraglutide group. There was no significant change in the plasma concentrations of the bone resorption marker CTX in either group [86]. These findings for P1NP/osteocalcin and CTX, markers of bone formation and resorption, respectively, suggest that the beneficial effect of liraglutide may be to promote bone formation rather than the prevention of bone resorption.…”
Section: Glp-1 Receptor Agonistsmentioning
confidence: 70%
See 1 more Smart Citation
“…Incretins are known suppressors of bone resorption, and it has previously been shown in vitro and in animal studies that GLP-1 reduces bone resorption (29,30,31). A recent clinical trial concluded that treatment with a GLP-1 analogue increases bone formation possibly by decreasing bone resorption in obese women (32). Patients with type 1 diabetes have normal postprandial levels of both GIP and GLP-1 (33), and traditionally, patients with type 2 diabetes are thought to have low levels of incretins, which would contribute to an impaired insulin response to hyperglycemia.…”
Section: Total (95% Ci)mentioning
confidence: 99%
“…A recent study in obese non-diabetic postmenopausal women taking liraglutide showed increased bone formation (elevation of P1NP without changes in CTX1) with prevention of bone loss even after weight loss due to the medication [110] . Studies in diabetic insulin-resistant rats show involvement of osteogenic activation of the Wnt pathway that can be reversed using exendin-4 [111].…”
Section: -Glp-1 and The Bonementioning
confidence: 93%